Global research priorities for youth mental health. Issue 1 (20th January 2020) - Mei, Cristina; Fitzsimons, Joanna; Allen, Nicholas; Alvarez‐Jimenez, Mario; Amminger, Günter Paul; Browne, Vivienne; Cannon, Mary; Davis, Maryann; Dooley, Barbara; Hickie, Ian B.; Iyer, Srividya; Killackey, Eóin; et al.
Abstract: Aim: Over the past two decades, the youth mental health field has expanded and advanced considerably. Yet, mental disorders continue to disproportionately affect adolescents and young adults. Their prevalence and associated morbidity and mortality in young people have not substantially reduced, with high levels of unmet need and poor access to evidence‐based treatments even in high‐income countries. Despite the potential return on investment, youth mental disorders receive insufficient funding. Motivated by these continual disparities, we propose a strategic agenda for youth mental health research. Method: Youth mental health experts and funders convened to develop youth mental health research priorities, via thematic roundtable discussions, that address critical evidence‐based gaps. Results: Twenty‐one global youth mental health research priorities were developed, including population health, neuroscience, clinical staging, novel interventions, technology, socio‐cultural factors, service delivery, translation and implementation. Conclusions: These priorities will focus attention on, and provide a basis for, a systematic and collaborative strategy to globally improve youth mental health outcomes.